The divine logos: the gender of the divine Jesus Christ in the Prologue to the Gospel of John - Webb, Maggie Rose Hermione (2024)
In this dissertation I will investigate the gender of the divine Jesus Christ, with reference to the prologue of John’s gospel, John 1.1-18. The main focus of this work will be on the use of the term Logos (Λόγος), a masculine term, to describe Christ, as well as the notion of pre-existence explored by the Johannine writer, and the implications of this for the gender of Christ. The corporeal Jesus was incarnated in the form of a human male, but I am exploring whether Jesus was fully male in divine self as well as in his human self, which involves considering what this key text tells us about the divine Christ, and whether it points to any divine significance of Jesus’ male gender. Although I will explore the nature of Christ’s divinity, my dissertation is in the context of the Johannine prologue, a text overtly establishing the divinity of Christ ‘Θεὸς ἦν ὁ Λόγος’ (John 1.1). I am subsequently not investigating whether Jesus was divine, as it is based on the assumption of Jesus’ divinity, as transcribed in this text. I therefore take Jesus Christ to be fully human and fully divine, in line with the later doctrine of the hypostatic union,1 which though is not a doctrine from the gospel of John, arguably has its theological backing in the high Christology of the Johannine Gospel. My hypothesis is that the text points to the divine Christ as genderless. This means that Jesus was genderless in divine aspect, but male in his humanity, making Jesus fully genderless and fully male in the same sense that Christ is fully divine and fully human. I will henceforth make the argument in this dissertation that the divine Jesus is genderless. The sections of my dissertation will be focused around Logos and Sophia, the pre-existence of Christ and the concept of a communal existence through Christ. I will begin by introducing the concept of gender, and my definition of this, before introducing the prologue of John’s gospel as a text, exploring the structure, function and content. The first and main section of my dissertation will examine Sophia, the Greek personified feminine wisdom principle, featured throughout the Septuagint, exploring the parallels between Logos and Sophia, to determine if Sophia and Logos are synonymous. I will make the claim that both are aspects of the second person of the trinity, Jesus Christ, but exploring the differences in the way that they function, using Philo’s conception of spoken and unspoken word, such that Sophia is the unspoken word, whereas the Logos is the external spoken word, manifesting in the world incarnate as Jesus Christ. This will involve interacting with the use of the term ‘Logos’ throughout the prologue, as well as some more specific verses, such as verses 16-17 which describe the relationship between Christ the Logos and the law. I will move on to explore the pre-existence of the Logos, as laid out from verse 1 of the prologue, and the implications of this for the separation of the physical male gender of Christ, and the eternal divine Logos form. The final section will explore the meaning of verse 3 of the prologue, ‘all things came into being through him’, determining the implications of this for the relationship between Jesus Christ and gender.